La ética y la responsabilidad social ante la pobreza (2012)
This paper describes a general situation of poverty in the world, defines some of its most salient causes, effects and possible solutions. Concentrates the problem in Latin America and specifically in Colombia. This article contains the meaning and criteria of social responsibility with an emphasis on that concerning companies or corporations. Includes policies and strategies to be practiced to effectively combat poverty, to eradicate poverty and reduce inequality. It emphasizes the role of CSR and international and multilateral agencies to achieve these goals and to contribute with moral persons and companies, either public or private to strive for the conditions that make possible a more equitable society, more involved in the economic development gains, less poor and endowed with more social welfare. In addition, this document underlies that the priority of the RS should be a frontal and constant fight against misery, poverty and unfair distribution of income and wealth that hurt most of the Latin American population.